How Positive Affect Modulates Cognitive Control: Reduced Perseveration at the Cost of Increased Distractibility - Dreisbach, Gesine; Goschke, Thomas (Journal of experimental psychology. Learning, memory, and cognition, 2004)
A fundamental problem that organisms face in a changing environment is how to regulate dynamically the balance between stable maintenance and flexible switching of goals and cognitive sets. The authors show that positive affect plays an important role in the regulation of this stability-flexibility balance. In a cognitive set-switching paradigm, the induction of mild increases in positive affect, as compared with neutral or negative affect, promoted cognitive flexibility and reduced perseveration, but also incurred a cost in terms of increased distractibility. Rather than influencing set switching in an unspecific way, positive affect thus exerted opposite effects on perseveration and distractibility. Results are consistent with neuropsychological models according to which effects of positive affect on cognitive control are mediated by increased dopamine levels in frontal brain areas.